EVANGELII GAUDIUM COMO ÊNFASE NA PRÁXIS LIBERTAÇÃO: opção preferencial pelos pobres, economia e utopia - Medeiros, Alexandre (2014)
The fundamental aspect of this research is the ecclesiastical document Apostolic Exhortation, Evangelii Gaudium the Joy of the Gospel, of the Pope Francisco, which was published in late 2013. This study is born from the works: A Theology of Liberation. Perspectives, of Gustavo Gutiérrez, first edition in 1971, and ninth in 2000, considered systematizing of Liberation Theology; has its development in Theology and Economics: rethinking liberation theology and utopias, of Jung Mo Sung, the fruit of his doctoral thesis 1993, published in 2008, which is a critical to the development of Liberation Theology; followed by Evangelii Gaudium the Joy of the Gospel, of the Pope Francisco, which was published in late 2013, first official document written by the hands of the elected pope. Therefore, we will study Gustavo Gutiérrez, Jung Mo Sung and ecclesiastical document of the Pope Francisco. The three initial chapters involve the preferential option for the poor, the economy and the utopia discussed individually in each thinker. Each author represents a different time, a different culture, but a common interest: concern with those that live on the periphery of the world. The fourth chapter will seek proximities between the ecclesiastical document and both authors studied. The research will follow the dialogical methodology, besides expanding the dialogue through bibliographic method. The goal is to find proximities and particularities between the authors and the ecclesiastical document. My hypothesis is that there is, in the document, similarities to the discourse of liberation theology. My interest is to seek a contribution of Christianity to the present day, in favor of a theology of life, against the mechanisms of death.